Power Sector Reforms and Electricity Supply Growth in Nigeria - Anwana, Edet Okon; Akpan, Boniface (Asian Journal of Economics and Empirical Research, 2016)
Adequate power supply constitutes the nucleus of operations and subsequently the engine of growth for all sectors of the economy. Despite the abundance of electricity generation sources in Nigeria, electricity distribution network and voltage profile are very poor resulting to more that 50 percent of the populace living without electricity supply. To salvage the electricity problem, the power sector has gone through some reforms, the major one being the enactment of the Electric Power Sector Reform Act of 2005. This was intended to restructure the electricity market from monopoly to a more competitive structure. This study is therefore undertaken to empirically evaluate the impacts of the reforms on electricity supply growth in the country. This study is based on the elementary supply theory. It covers from 1981 to 2015. Econometric approach for the study relies on time series data regression. The study adopted the contemporary econometric approach of error correction mechanism (ECM). The results showed that all the variables were stationary and statistically significant. There exist a unique long-run equilibrium relationship between all the variables of the model and so, cointegrated and normalized coefficients were reported. ECM results revealed the speed of adjustment of 92.1 percent between the short-run and the long-run behaviors of electricity supply with its independent variables. From the analysis, reforms’ coefficient (REF) had a positive sign but statistically insignificant. The other variables, electricity price (ELP), government investment in the power sector (GOVINV), annual rainfall (RAIN) and per capita GDP (PCGDP) conformed to apriori expectations in terms of sign and were statistically significant. The study concludes that the present reform efforts in the power sector will bring great improvements in the power sector of the country if properly harnessed. From the results, the study recommends that government should totally transfer ownership in all electricity production and supply chain to the private investors and only monitor or regulate the market.